Osteophyte formation causes neurological symptoms after anterior cervical discectomy and fusion (ACDF): A case report - Jin, Haiming; Luo, Jiangtao; Jiang, Yuhan; Lin, Jinghao; Jiang, Junchen; Ren, Rufeng; Fang, Weiyuan; Wu, Yaosen; Wang, Xiangyang (Frontiers in Surgery, 2023)
Spinal surgeons have been drawn to the incidence of osteophytes following intervertebral disc degeneration in clinical practice. However, the production of osteophytes, particularly in the spinal canal, after anterior cervical discectomy and fusion (ACDF) is uncommon. We described a 42-year-old male patient who underwent C4–6 ACDF due to cervical stenosis two years prior in another public hospital in the province. His primary symptoms were significantly relieved, but he developed new pain and weakness in his right leg six months after surgery. The imaging results revealed a large posterior osteophyte at C5/6, compressing the spinal cord anteriorly. Accordingly, we performed cervical open-door laminoplasty to decompress the spinal cord. The patient's clinical symptoms had significantly improved at the one-year follow-up. This case seeks to inform surgeons that cautious, routine follow-ups are necessary for the event that a severe intracanal osteophyte develops at the operated level following ACDF. The comprehensive osteophyte removal and strong fixation at the operative level during ACDF warrant more consideration as these procedures may lower the incidence of new osteophytes. Additionally, surgical procedures may be required.